The activities of prince Francis-Xaveriy Drucky-Lubetsky to restore Russian administration in Grodno province in 1813 - Lukashevich, Andrei M. (Journal of the Belarusian State University. History, 2025)
The article reveals the main areas of activity of the acting Grodno civil governor (January – March 1813) prince Francis-Xaveriy (in Russian service – Xaveriy Frantsevich, or K. F.) Drucky-Lubetsky (1778–1846). The circumstances of the official’s appointment and the reasons for his quick recall from office are revealed. The article details the prince’s role in the activities of the temporary Grodno provincial executive commission, formed in January 1813 by the Lithuanian military governor A. M. Rimsky-Korsakov as a transitional administration. The article shows the role of prince K. F. Drucky-Lubetsky in organising provisions and forage supplies for Russian troops, as well as in collecting taxes and duties in the Grodno province. The article traces the prince’s involvement in the fate of prisoners of war of the Grand Army, mobilised in 1812 in the Belarusian-Lithuanian provinces, as well as in the resumption of the activities of the treasury chamber and judicial institutions (the Main Court, city courts). It is noted that prince K. F. Drucky-Lubetsky was involved in the creation of lustration commissions and the resumption of the work of the Main Committee for Military Duties, designed to ensure the collection of information on the material damage inflicted on the residents of the region in 1812. It is concluded that the rapid rise and growth of influence of prince K. F. Drucky-Lubetsky in 1813 were due to the special trust of the Russian Emperor Alexander I in him, which, in turn, was a consequence of the prince’s loyalty to Russia. It is determined that the intrigues against the prince by a number of ill-wishers from among the military (Grodno commandant) and civil servants (Grodno vice-governor) were unable to have a significant impact on the career growth of the official during the period under review.
Keywords: Grodno province; civil governor; provincial marshal; K. F. Drucky-Lubetsky; A. M. Rimsky-Korsakov; provincial executive commission; provision of troops